Ammonia stable combustion catalyst composition as well as preparation method and application thereof

By using a catalyst composition consisting of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxides and modified CFB boiler fly ash in CFB boilers, the problems of difficult ignition and poor stability of ammonia combustion in CFB boilers are solved, efficient ammonia decomposition and combustion are achieved, costs are reduced, and the strength and dispersion effect of the catalyst are improved.

CN120605727APending Publication Date: 2025-09-09CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410252662.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

Existing ammonia combustion technology in circulating fluidized bed boilers has problems such as difficult ignition, low laminar flame speed, poor stability, and low combustion efficiency. In particular, it is difficult to adapt to the high-temperature operating conditions of the CFB boiler furnace during high-proportion ammonia combustion.

Method used

A catalyst composition consisting of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structural oxide, modified CFB boiler fly ash, MgAl2O4 and activated alumina is used to improve combustion stability and efficiency by decomposing NH3 to generate H2 inside the CFB boiler.

Benefits of technology

Under CFB boiler operating conditions, it promotes the decomposition and combustion of ammonia, improves combustion efficiency, reduces costs and achieves waste recycling, and enhances the strength and dispersion effect of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004728125930000151
    Figure BDA0004728125930000151
  • Figure BDA0004728125930000152
    Figure BDA0004728125930000152
Patent Text Reader

Abstract

The invention discloses an ammonia stable combustion catalyst composition and a preparation method and application thereof, and the ammonia stable combustion catalyst composition comprises the following components by weight: (a) 25-60 wt% of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide; (b) 10 to 50 weight percent of modified CFB (circulating fluid bed) boiler fly ash; (c) 5 to 30 weight percent of MgAl2O4 (MgAl2O4); and (d) 10 to 30 weight percent of activated aluminum oxide. The ammonia stable combustion catalyst composition is added into a CFB (circulating fluid bed) hearth, and partially catalyzes and decomposes NH3 into H2 in the hearth under the working conditions that circulating materials flow in the hearth-separator-return feeder-hearth, NH3 is doped in the CFB boiler for combustion, and particularly high-proportion NH3-doped combustion is carried out, so that the ammonia-doped combustion stability and combustion efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ammonia combustion catalysts, and in particular relates to an ammonia stable combustion catalyst composition, a preparation method and an application thereof. Background Art

[0002] Circulating fluidized bed (CFB) boilers, one of the most commercially successful clean coal combustion technologies, have been widely adopted due to their excellent fuel adaptability, load regulation, and ash and slag comprehensive utilization. However, they are also a major source of CO2 emissions. Energy conservation and emission reduction measures, including the use of renewable energy, can reduce or offset CO2 emissions from CFB boiler combustion. NH3, a hydrogen-rich, carbon-free fuel, offers advantages such as high energy density, low cost, and safe storage and transportation. Its combined combustion with coal is considered a rapid and effective method for reducing CO2 emissions.

[0003] However, the NH3 combustion process has some drawbacks, such as difficulty in ignition, low laminar flame speed, poor stability, and relatively low combustion efficiency. To address these drawbacks, existing stable combustion technologies mainly include: (1) fuel optimization, such as co-combustion with fuels with better reaction performance, such as H2, CH4, CO, dimethyl ether, etc.; (2) heat and mass transfer enhancement, such as changing the reaction temperature and O2 concentration during the reaction process; and (3) plasma combustion assistance. Existing studies have found that the addition of NH3 mixed with H2 can significantly promote the ignition of ammonia. Even if 1% (volume fraction) H2 is added, the ignition delay time of ammonia will be significantly shortened. The higher the proportion of H2 mixed, the more obvious the effect of improving the stable combustion of NH3.

[0004] In the combustion process of NH3-doped CFB boilers, especially in the combustion process of high-proportion NH3-doped, introducing H2 from the outside is a strategy to improve the stable combustion of NH3, and partially decomposing NH3 to produce H2 is another more effective measure. The NH3 decomposition catalysts that are currently being studied mainly include ruthenium-based, iron-based, nickel-based, cobalt-based, transition metal carbides and nitrides, etc. Chinese patent application No. 202110478047.9 discloses an ammonia decomposition catalyst, a preparation method and application thereof. The preparation method of the ammonia decomposition catalyst provided comprises the following steps: ball milling ruthenium acetate, magnesium acetate and potassium acetate to obtain a metal salt mixture powder; calcining the metal salt mixture powder, and then reducing it with hydrogen to obtain the ammonia decomposition catalyst. Chinese Patent Application No. 202110174212.1 discloses a low-temperature activated, high-efficiency ammonia decomposition catalyst and its preparation method, belonging to the field of ammonia decomposition catalysis. The catalyst is a nickel-containing FER molecular sieve. The molecular sieve uses a nickel-containing carbon material as a nickel source and hard template, and metallic nickel is in situ introduced into the FER molecular sieve. The nickel content of the nickel-containing molecular sieve is 0.1-5% by weight, calculated as elemental nickel. Chinese Patent Application No. 202111649228.X discloses a method for preparing a large-scale, high-pressure ammonia decomposition catalyst. This catalyst uses Al2O3 and MgO as carriers, rare earth metals as additives, and nickel and iron as the main active components. The main mass percentages are: NiO: 15%-30%, Fe2O3: 10%-30%, Al2O3: 35%-50%, MgO: 10%-30%, and rare earth metal oxides: 0.5%-3%. Chinese patent application number 202010501059.4 discloses a catalyst support, an ammonia decomposition catalyst, and a preparation method. The support is carbon-modified boron nitride, with a carbon doping level of 1-8% based on the total weight of the support. The catalysts covered in these patents are generally used in specially formulated fixed-bed reactors for NH3 decomposition at temperatures of 500-600°C, making them difficult to adapt to the operating temperatures of 850-920°C inside CFB boiler furnaces. Summary of the Invention

[0005] In response to the deficiencies in the prior art, the present invention aims to provide an ammonia-stable combustion catalyst composition, a preparation method, and an application thereof. The ammonia-stable combustion catalyst composition prepared by the present invention is added to the interior of a CFB furnace. As the circulating material flows through the furnace-separator-returner-furnace, the CFB boiler is mixed with NH3 for combustion, especially under high-proportion NH3-mixed combustion conditions. Part of the NH3 is catalytically decomposed into H2 in the furnace, thereby improving the stability and combustion efficiency of ammonia-mixed combustion.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] An ammonia-stabilized combustion catalyst composition comprising the following components, calculated on the weight of the composition:

[0008] (a) 25-60 wt% of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0009] (b) 10-50 wt% of modified CFB boiler fly ash;

[0010] (c) 5-30 wt% MgAl2O4;

[0011] (d) 10-30 wt% of activated alumina.

[0012] An ammonia-stabilized combustion catalyst composition comprising the following components, calculated on the weight of the composition:

[0013] (a) 30-55 wt% of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0014] (b) 15-45 wt% of modified CFB boiler fly ash;

[0015] (c) 10-25 wt% MgAl2O4;

[0016] (d) 12-25 wt% activated alumina.

[0017] Preferably, the mass ratio of Fe2O3:CoO:TiO2 in the component (a) is (1.0-3.0):(1.0-2.0):(0.3-1.0).

[0018] Preferably, the preparation method of component (a) is as follows:

[0019] S1. Mix dodecylamine and water uniformly, and add n-butanol under stirring to obtain a microemulsion liquid;

[0020] S2. Add ferrous nitrate, cobalt nitrate and titanium tetrachloride to the microemulsion liquid in step S1, stir and dissolve, then add ammonia water to adjust the pH, and perform hydrothermal crystallization reaction. After the reaction is completed, centrifuge, filter, wash and dry to obtain Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide, i.e., the component (a).

[0021] Preferably, the mass ratio of dodecylamine, water and n-butanol in step S1 is 10:130-160:100-140.

[0022] Preferably, the temperature of the hydrothermal crystallization reaction in step S2 is 110-150° C., and the time is 20-30 hours.

[0023] Preferably, the preparation method of the component (b) is as follows: CFB boiler fly ash is roasted, washed after roasting, then added into a citric acid-lactic acid mixed aqueous solution for acidification, filtered and dried after treatment to obtain the component (b).

[0024] Preferably, the calcination temperature is 500-700° C., and the time is 3-5 hours; the concentration of citric acid in the citric acid-lactic acid aqueous solution is 10-15wt%, and the concentration of lactic acid is 5-10wt%; and the acidification treatment time is 6-10 hours.

[0025] The present invention also protects a method for preparing the ammonia-stabilized combustion catalyst composition, comprising the following steps:

[0026] Component (d) is added to deionized water, stirred evenly, and then hydrochloric acid with a mass concentration of 36% is added, where the amount of hydrochloric acid added is 25-30wt% of component (d), and stirred into a sol state. Components (a), (b), and (c) are then added and stirred for 4-6 hours to form a uniform slurry. After homogenization, the slurry is aged for 8-24 hours, dried at 120-140°C, and then calcined at 750-900°C for 10-24 hours. The slurry is crushed and sieved through a 60-450μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0027] The present invention also protects the use of the ammonia stable combustion catalyst composition in a circulating fluidized bed boiler.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention provides an ammonia stable combustion catalyst composition with an iron-cobalt-titanium ternary hydrotalcite as an active component. The composition can reduce the activation energy of the ammonia decomposition reaction and promote the decomposition and combustion of ammonia under CFB boiler operating conditions. The high pore volume and specific surface area of ​​the activated alumina provide a good dispersion effect for the active component, further improving the ammonia decomposition performance of the active component. The interaction between MgAl2O4 and the activated alumina increases the strength of the catalyst composition. CFB boiler fly ash contains relatively high levels of effective components such as Al2O3, Fe2O3 and TiO2. The addition of fly ash can reduce costs and promote waste recycling. The modified fly ash can change its acidity, improve the bonding properties of other components of the fly ash, and thus improve the strength of the catalyst composition. DETAILED DESCRIPTION

[0030] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0031] An ammonia-stabilized combustion catalyst composition comprising the following components, calculated on the weight of the composition:

[0032] (a) 25-60 wt% of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0033] (b) 10-50 wt% of modified CFB boiler fly ash;

[0034] (c) 5-30 wt% MgAl2O4;

[0035] (d) 10-30 wt% of activated alumina.

[0036] Preferably, the content of component (a) may be 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, preferably 30-55 wt%.

[0037] Preferably, the content of component (b) can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, preferably 15-45wt%.

[0038] Preferably, the content of component (c) may be 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, preferably 10-25 wt%.

[0039] Preferably, the content of component (d) may be 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, preferably 12-25 wt%.

[0040] Furthermore, the mass ratio of Fe2O3:CoO:TiO2 in the component (a) is (1.0-3.0):(1.0-2.0):(0.3-1.0), which can be 1:1:0.3, 1:2:0.3, 2:1:0.3, 3:1:0.3, 2:2:0.3, 3:2:0.3, 1:1:0.5, 1:2:0.5, 2:1:0.5, 3:1:0.5, 2:2:0.5, 3:2:0.5, 1:1:1, 1:2:1, 2:1:0.5, 3:1:1, 2:2:1, 3:2:1.

[0041] Preferably, the preparation method of component (a) is as follows:

[0042] S1. Mix dodecylamine and water uniformly, and add n-butanol under stirring to obtain a microemulsion liquid;

[0043] S2. Add ferrous nitrate, cobalt nitrate and titanium tetrachloride to the microemulsion liquid in step S1, stir and dissolve, then add ammonia water to adjust the pH, and perform hydrothermal crystallization reaction. After the reaction is completed, centrifuge, filter, wash and dry to obtain Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide, i.e., the component (a).

[0044] Furthermore, the mass ratio of dodecylamine, water and n-butanol in step S1 is 10:130-160:100-140, and can be 10:130:100, 10:140:100, 10:150:100, 10:160:100, 10:130:120, 10:140:120, 10:150:120, 10:160:120, 10:130:140, 10:140:140, 10:150:140, 10:160:140.

[0045] Furthermore, the temperature of the hydrothermal crystallization reaction in step S2 is 110-150°C, which can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, or 150°C, and the time is 20-30h, which can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, or 30h.

[0046] Preferably, the preparation method of the component (b) is as follows: CFB boiler fly ash is roasted, washed after roasting, then added into a citric acid-lactic acid mixed aqueous solution for acidification, filtered and dried after treatment to obtain the component (b).

[0047] Further, the roasting temperature is 500-700°C, which can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, and the time is 3-5h, which can be 3h, 3.5h, 4h, 4.5h, 5h; the lemon The concentration of citric acid in the citric acid-lactic acid aqueous solution is 10-15wt%, which can be 11wt%, 12wt%, 13wt%, 14wt%, or 15wt%; the concentration of lactic acid is 5-10wt%, which can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%; and the time for the acidification treatment is 6-10h, which can be 6.5h, 7h, 7.5h, 8h, 6.5h, 8.5h, 9h, 9.5h, or 10h.

[0048] Preferably, a method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0049] Component (d) is added to deionized water, stirred evenly, and then hydrochloric acid with a mass concentration of 36% is added, where the amount of hydrochloric acid added is 25-30wt% of component (d), and stirred into a sol state. Components (a), (b), and (c) are then added and stirred for 4-6 hours to form a uniform slurry. After homogenization, the slurry is aged for 8-24 hours, dried at 120-140°C, and then calcined at 750-900°C for 10-24 hours. The slurry is crushed and sieved through a 60-450μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0050] Furthermore, the aging time can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h; the drying temperature can be 120℃, 125℃, 130℃, 135℃, 140℃; the roasting temperature can be 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, and the time can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h.

[0051] Example 1

[0052] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0053] (1) Preparation of Fe2O3-CoO-TiO2 ternary hydrotalcite-like oxide: 111.5 g of dodecylamine was weighed and added to 1500 mL of deionized water and mixed evenly. 1000 mL of n-butanol was added under stirring. After dodecylamine was completely dissolved in n-butanol to obtain a microemulsion, 222.8 g of Fe(NO3)3·9H2O (content 98.5%) and 170.6 g of TiO2 were added. Co(NO3)2·6H2O (content 99.0%) and 31.6gTiCl4 (content 99.5%) (mass ratio Fe2O3:CoO:TiO2=1.0:1.0:0.3) were stirred until the solid was completely dissolved, 10wt% ammonia water was added dropwise to adjust the pH to 7.5, and then the mixture was transferred to a 5000mL reactor and subjected to hydrothermal crystallization reaction at 120°C for 24h. After the reaction was completed, the mixture was centrifuged, washed twice with water, washed twice with alcohol, and dried at 60°C to obtain the Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0054] (2) Preparation of modified CFB boiler fly ash: 500 g of ground CFB boiler fly ash with a particle size of <50 μm was calcined at 600°C for 4 h, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid were weighed and placed in a beaker, 1200 mL of deionized water was added, and stirred to completely dissolve, followed by adding 500 g of treated CFB boiler fly ash, stirring for 3 h, allowing to stand for 5 h, filtering, and drying at 70°C to obtain modified CFB boiler fly ash;

[0055] (3) Preparation of an ammonia-stabilized combustion catalyst composition: 10 g of activated alumina with a particle size of <50 μm was placed in a beaker, 200 mL of deionized water was added, and the mixture was stirred evenly. Then, 2.5 g of a 36% hydrochloric acid solution was slowly added dropwise. After the addition was completed, the mixture was vigorously stirred to form a sol. Subsequently, 22.5 g of a ternary hydrotalcite-like structured oxide of Fe2O3-CoO-TiO2, 7.5 g of a modified CFB boiler fly ash, and 10 g of MgAl2O4 were added. The mixture was stirred for 5 h, homogenized, aged for 18 h, dried at 120°C, and then calcined at 850°C for 12 h. The mixture was crushed and sieved through a 100 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0056] Example 2

[0057] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0058] (1) Preparation of Fe2O3-CoO-TiO2 ternary hydrotalcite-like oxide: 111.5 g of dodecylamine was weighed and added to 1500 mL of deionized water and mixed evenly. 1000 mL of n-butanol was added under stirring. After dodecylamine was completely dissolved in n-butanol to obtain a microemulsion, 240.4 g of Fe(NO3)3·9H2O (content 98.5%) and 147.1 g of TiO2 were added. Co(NO3)2·6H2O (content 99.0%) and 37.4gTiCl4 (content 99.5%) (mass ratio Fe2O3:CoO:TiO2=1.5:1.2:0.5) were stirred until the solid was completely dissolved, 10wt% ammonia water was added dropwise to adjust the pH to 7.5, and then the mixture was transferred to a 5000mL reactor and hydrothermally crystallized at 120°C for 24h. After the reaction was completed, the mixture was centrifuged, washed twice with water, washed twice with alcohol, and dried at 60°C to obtain the Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0059] (2) Preparation of modified CFB boiler fly ash: 500 g of ground CFB boiler fly ash with a particle size of <50 μm was calcined at 500°C for 5 h, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid were weighed and placed in a beaker, 1200 mL of deionized water was added, and stirred to completely dissolve, followed by adding 500 g of treated CFB boiler fly ash, stirring for 4 h, allowing to stand for 4 h, filtering, and drying at 70°C to obtain modified CFB boiler fly ash;

[0060] (3) Preparation of an ammonia-stabilized combustion catalyst composition: 7.5 g of activated alumina with a particle size of <50 μm was placed in a beaker, 200 mL of deionized water was added, and the mixture was stirred evenly. Then, 1.9 g of a 36% hydrochloric acid solution was slowly added dropwise. After the addition was completed, the mixture was vigorously stirred to form a sol. Subsequently, 20 g of a ternary hydrotalcite-like structured oxide of Fe2O3-CoO-TiO2, 17.5 g of a modified CFB boiler fly ash, and 5 g of MgAl2O4 were added. The mixture was stirred for 5 h, homogenized, aged for 18 h, dried at 130°C, and then calcined at 870°C for 14 h. The mixture was crushed and sieved through a 200 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0061] Example 3

[0062] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0063] (1) Preparation of Fe2O3-CoO-TiO2 ternary hydrotalcite-like oxide: 111.5 g of dodecylamine was weighed and added to 1500 mL of deionized water and mixed evenly. 1000 mL of n-butanol was added under stirring. After dodecylamine was completely dissolved in n-butanol to obtain a microemulsion, 256.4 g of Fe(NO3)3·9H2O (content 98.5%) and 147.1 g of TiO2 were added. Co(NO3)2·6H2O (content 99.0%) and 37.4gTiCl4 (content 99.5%) (mass ratio Fe2O3:CoO:TiO2=2.0:1.5:0.5) were stirred until the solid was completely dissolved, 10wt% ammonia water was added dropwise to adjust the pH to 7.5, and then the mixture was transferred to a 5000mL reactor and hydrothermally crystallized at 120°C for 24h. After the reaction was completed, the mixture was centrifuged, washed twice with water, washed twice with alcohol, and dried at 60°C to obtain the Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0064] (2) Preparation of modified CFB boiler fly ash: 500 g of ground CFB boiler fly ash with a particle size of <50 μm was calcined at 600°C for 4 h, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid were weighed and placed in a beaker, 1200 mL of deionized water was added, and stirred to completely dissolve, followed by adding 500 g of treated CFB boiler fly ash, stirring for 3 h, allowing to stand for 5 h, filtering, and drying at 70°C to obtain modified CFB boiler fly ash;

[0065] (3) Preparation of an ammonia-stabilized combustion catalyst composition: 7.5 g of activated alumina with a particle size of <50 μm was placed in a beaker, 200 mL of deionized water was added, and the mixture was stirred evenly. Then, 1.9 g of a 36% hydrochloric acid solution was slowly added dropwise. After the addition was completed, the mixture was vigorously stirred to form a sol. Subsequently, 25 g of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide, 10 g of modified CFB boiler fly ash, and 7.5 g of MgAl2O4 were added. The mixture was stirred for 5 h, homogenized, aged for 18 h, dried at 130°C, and then calcined at 900°C for 16 h. The mixture was crushed and sieved through a 60 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0066] Example 4

[0067] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0068] (1) Preparation of Fe2O3-CoO-TiO2 ternary hydrotalcite-like oxide: 111.5 g of dodecylamine was weighed and added to 1500 mL of deionized water and mixed evenly. 1000 mL of n-butanol was added under stirring. After dodecylamine was completely dissolved in n-butanol to obtain a microemulsion, 285 g of Fe(NO3)3·9H2O (content 98.5%), 87.1 g of Co(NO3)2·6H2O (content 99.0%) and 53.2 g of TiCl4 (content 99.5%) (mass ratio of Fe2O3:CoO:TiO2=2.5:1.0:1.0), stirred until the solid was completely dissolved, and 10wt% ammonia water was added dropwise to adjust the pH to 7.5, then transferred to a 5000mL reactor, and hydrothermally crystallized at 120°C for 24h. After the reaction was completed, centrifuged, washed twice with water, washed twice with alcohol, and dried at 60°C to obtain the Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0069] (2) Preparation of modified CFB boiler fly ash: 500 g of ground CFB boiler fly ash with a particle size of <50 μm was calcined at 700°C for 3 h, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid were weighed and placed in a beaker, 1200 mL of deionized water was added, and stirred to completely dissolve, followed by adding 500 g of treated CFB boiler fly ash, stirring for 6 h, allowing to stand for 4 h, filtering, and drying at 70°C to obtain modified CFB boiler fly ash;

[0070] (3) Preparation of an ammonia-stabilized combustion catalyst composition: 9 g of activated alumina with a particle size of <50 μm was placed in a beaker, 200 mL of deionized water was added, and the mixture was stirred evenly. Then, 2.3 g of a 36% hydrochloric acid solution was slowly added dropwise. After the addition was completed, the mixture was vigorously stirred to form a sol. Subsequently, 16 g of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide, 20 g of modified CFB boiler fly ash, and 5 g of MgAl2O4 were added. The mixture was stirred for 5 h, homogenized, aged for 18 h, dried at 140°C, and then calcined at 875°C for 16 h. The mixture was crushed and sieved through a 300 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0071] Example 5

[0072] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0073] (1) Preparation of Fe2O3-CoO-TiO2 ternary hydrotalcite-like oxide: 111.5 g of dodecylamine was weighed and added to 1500 mL of deionized water and mixed evenly. 1000 mL of n-butanol was added under stirring. After dodecylamine was completely dissolved in n-butanol to obtain a microemulsion, 279.8 g of Fe(NO3)3·9H2O (content 98.5%) and 142.6 g of TiO2 were added. Co(NO3)2·6H2O (content 99.0%) and 21.77gTiCl4 (content 99.5%) (mass ratio Fe2O3:CoO:TiO2=3.0:2.0:0.5) were stirred until the solid was completely dissolved, 10wt% ammonia water was added dropwise to adjust the pH to 7.5, and then the mixture was transferred to a 5000mL reactor and hydrothermally crystallized at 120°C for 24h. After the reaction was completed, the mixture was centrifuged, washed twice with water, washed twice with alcohol, and dried at 60°C to obtain the Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0074] (2) Preparation of modified CFB boiler fly ash: 500 g of ground CFB boiler fly ash with a particle size of <50 μm was calcined at 600°C for 4 h, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid were weighed and placed in a beaker, 1200 mL of deionized water was added, and stirred to completely dissolve, followed by adding 500 g of treated CFB boiler fly ash, stirring for 3 h, allowing to stand for 5 h, filtering, and drying at 70°C to obtain modified CFB boiler fly ash;

[0075] (3) Preparation of an ammonia-stabilized combustion catalyst composition: 10 g of activated alumina with a particle size of <50 μm was placed in a beaker, 200 mL of deionized water was added, and the mixture was stirred evenly. Then, 2.5 g of a 36% hydrochloric acid solution was slowly added dropwise. After the addition was completed, the mixture was vigorously stirred to form a sol. Subsequently, 27.5 g of a ternary hydrotalcite-like structured oxide of Fe2O3-CoO-TiO2, 7.5 g of a modified CFB boiler fly ash, and 5 g of MgAl2O4 were added. The mixture was stirred for 5 h, homogenized, aged for 20 h, dried at 140°C, and then calcined at 750°C for 24 h. The mixture was crushed and sieved through a 100 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0076] Example 6

[0077] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0078] (1) Preparation of Fe2O3-CoO-TiO2 ternary hydrotalcite-like oxide: 111.5 g of dodecylamine was weighed and added to 1500 mL of deionized water and mixed evenly. 1000 mL of n-butanol was added under stirring. After dodecylamine was completely dissolved in n-butanol to obtain a microemulsion, 192.4 g of Fe(NO3)3·9H2O (content 98.5%), 98.0 g of Co(NO3)2·6H2O (content 99.0%) and 89.8 g of TiCl4 (content 99.5%) (mass ratio of Fe2O3:CoO:TiO2=1.5:1.0:1.5), stirred until the solid was completely dissolved, and 10wt% ammonia water was added dropwise to adjust the pH to 7.5, then transferred to a 5000mL reactor, and hydrothermally crystallized at 120°C for 24h. After the reaction was completed, centrifuged, washed twice with water, washed twice with alcohol, and dried at 60°C to obtain the Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide;

[0079] (2) Preparation of modified CFB boiler fly ash: 500 g of ground CFB boiler fly ash with a particle size of <50 μm was calcined at 600°C for 4 h, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid were weighed and placed in a beaker, 1200 mL of deionized water was added, and stirred to completely dissolve, followed by adding 500 g of treated CFB boiler fly ash, stirring for 3 h, allowing to stand for 5 h, filtering, and drying at 70°C to obtain modified CFB boiler fly ash;

[0080] (3) Preparation of an ammonia-stabilized combustion catalyst composition: 7.5 g of activated alumina with a particle size of <50 μm was placed in a beaker, 200 mL of deionized water was added, and the mixture was stirred evenly. Then, 1.9 g of a 36% hydrochloric acid solution was slowly added dropwise. After the addition was completed, the mixture was vigorously stirred to form a sol. Subsequently, 15 g of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide, 22.5 g of modified CFB boiler fly ash, and 5 g of MgAl2O4 were added. The mixture was stirred for 5 h, homogenized, aged for 24 h, dried at 140°C, and then calcined at 850°C for 20 h. The mixture was crushed and sieved through a 300 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0081] Comparative Example 1

[0082] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0083] 222.8 g of Fe(NO3)3·9H2O (content 98.5%), 170.6 g of Co(NO3)2·6H2O (content 99.0%) and 31.6 g of TiCl4 (content 99.5%) were dissolved in 1500 mL of deionized water, followed by the addition of 7.5 g of CFB boiler fly ash with a ground particle size of <50 μm and 10 g of MgAl2O4; stirring was continued for 5 h, and the mixture was homogenized and aged for 18 h, dried at 120° C., and then calcined at 850° C. for 12 h, crushed, and sieved through a 100 μm sieve to obtain the ammonia-stabilized combustion catalyst composition.

[0084] Comparative Example 2

[0085] A method for preparing an ammonia-stabilized combustion catalyst composition comprises the following steps:

[0086] 222.8 g of Fe(NO3)3·9H2O (content 98.5%), 170.6 g of Co(NO3)2·6H2O (content 99.0%), and 31.6 g of TiCl4 (content 99.5%) were dissolved in 1500 mL of deionized water, followed by the addition of 7.5 g of modified CFB boiler fly ash and 10 g of MgAl2O4; the mixture was stirred for 5 h, homogenized, aged for 18 h, dried at 120° C., and then calcined at 850° C. for 12 h, crushed, and sieved through a 100 μm sieve to obtain the ammonia-stabilized combustion catalyst composition;

[0087] The modified CFB boiler fly ash is prepared as follows: 500 g of ground CFB boiler fly ash with a particle size of less than 50 μm is calcined at 600° C. for 4 hours, then washed with distilled water, allowed to stand until neutral, and filtered to obtain treated CFB boiler fly ash; 154 g of citric acid and 72 g of lactic acid are weighed and placed in a beaker, 1200 mL of deionized water is added, and stirred to completely dissolve, followed by adding 500 g of the treated CFB boiler fly ash, stirring for 3 hours, standing for 5 hours, filtering, and drying at 70° C. to obtain modified CFB boiler fly ash.

[0088] The ammonia decomposition performance of the ammonia-stabilized combustion catalysts prepared in Examples 1-6 and Comparative Examples 1-2 was evaluated as follows. The ammonia decomposition evaluation test was conducted in a fixed-bed reactor. 5 g of the catalyst was mixed with quartz sand of the same mesh size at a volume ratio of 1:1. The reaction gas was (60 vol% NH3, 40 vol% N2) at a flow rate of 120 mL / min, the reaction temperature was 870°C, and the reaction pressure was atmospheric pressure. The H2 and NH3 contents generated by the reaction were analyzed, and the ammonia decomposition performance of the ammonia-stabilized combustion catalyst was evaluated based on the NH3 conversion rate, as shown in Equation (1). The performance evaluation results are shown in Table 1.

[0089]

[0090] Where: η is the NH3 conversion rate, C NH3 is the NH3 concentration in the mixed gas after the reaction, vol%, C NH3a is the NH3 concentration in the mixed gas before the reaction (vol%).

[0091] Table 1 Ammonia decomposition performance of ammonia stable combustion catalyst

[0092]

[0093] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. An ammonia-stabilized combustion catalyst composition, characterized in that: The composition comprises the following components by weight: (a) 25-60 wt% of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide; (b) 10-50 wt% of modified CFB boiler fly ash; (c) 5-30 wt% MgAl2O4; (d) 10-30 wt% of activated alumina.

2. The ammonia-stabilized combustion catalyst composition according to claim 1, characterized in that: The composition comprises the following components by weight: (a) 30-55 wt% of Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide; (b) 15-45 wt% of modified CFB boiler fly ash; (c) 10-25 wt% MgAl2O4; (d) 12-25 wt% activated alumina.

3. The ammonia-stabilized combustion catalyst composition according to claim 1, characterized in that: The mass ratio of Fe2O3:CoO:TiO2 in the component (a) is (1.0-3.0):(1.0-2.0):(0.3-1.0).

4. The ammonia-stabilized combustion catalyst composition according to claim 1, characterized in that: The preparation method of the component (a) is as follows: S1. Mix dodecylamine and water uniformly, and add n-butanol under stirring to obtain a microemulsion liquid; S2. Add ferrous nitrate, cobalt nitrate and titanium tetrachloride to the microemulsion liquid in step S1, stir and dissolve, then add ammonia water to adjust the pH, and perform hydrothermal crystallization reaction. After the reaction is completed, centrifuge, filter, wash and dry to obtain Fe2O3-CoO-TiO2 ternary hydrotalcite-like structure oxide, i.e., the component (a).

5. The ammonia-stabilized combustion catalyst composition according to claim 4, characterized in that: The mass ratio of dodecylamine, water and n-butanol in step S1 is 10:130-160:80-120.

6. The ammonia-stabilized combustion catalyst composition according to claim 4, characterized in that: The temperature of the hydrothermal crystallization reaction in step S2 is 110-150° C., and the time is 20-30 hours.

7. The ammonia-stabilized combustion catalyst composition according to claim 1, characterized in that: The preparation method of the component (b) is as follows: CFB boiler fly ash is roasted, washed after roasting, and then added into a mixed aqueous solution of citric acid and lactic acid for acidification treatment. After the treatment, the mixture is filtered and dried to obtain the component (b).

8. The ammonia-stabilized combustion catalyst composition according to claim 7, characterized in that: The calcination temperature is 500-700° C. and the calcination time is 3-5 hours. The concentration of citric acid in the citric acid-lactic acid aqueous solution is 10-15wt%, and the concentration of lactic acid is 5-10wt%. The acidification treatment time is 6-10 hours.

9. A method for preparing the ammonia-stabilized combustion catalyst composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: Component (d) is added to deionized water, stirred evenly, and then hydrochloric acid with a mass concentration of 36% is added, where the amount of hydrochloric acid added is 25-30wt% of component (d), and stirred into a sol state. Components (a), (b), and (c) are then added and stirred for 4-6 hours to form a uniform slurry. After homogenization, the slurry is aged for 8-24 hours, dried at 120-140°C, and then calcined at 750-900°C for 10-24 hours and crushed to obtain the ammonia-stabilized combustion catalyst composition.

10. Use of the ammonia-stabilized combustion catalyst composition according to any one of claims 1 to 8 in a circulating fluidized bed boiler.

Citation Information

Patent Citations

  • Catalyst carrier, ammonia decomposition catalyst and preparation method

    CN111790420A

  • Low-temperature activation efficient ammonia decomposition catalyst

    CN113181957A

  • Ammonia decomposition catalyst and preparation method and application thereof

    CN113289693A

  • Large-scale high-pressure ammonia decomposition catalyst and preparation method thereof

    CN114160150A